2020
DOI: 10.1038/s41401-019-0351-4
|View full text |Cite
|
Sign up to set email alerts
|

Chalcomoracin inhibits cell proliferation and increases sensitivity to radiotherapy in human non-small cell lung cancer cells via inducing endoplasmic reticulum stress-mediated paraptosis

Abstract: Chalcomoracin (CMR) is a kind of Diels–Alder adduct extracted from the mulberry leaves. Recent studies showed that CMR has a broad spectrum of anticancer activities and induces paraptosis in breast cancer and prostate cancer cells. In this study, we investigated the effects of CMR against human non-small cell lung cancer cells and the underlying mechanisms. We found that CMR dose-dependently inhibited the proliferation of human lung cancer H460, A549 and PC-9 cells. Furthermore, exposure to low and median dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Clinically, drugs that activate ER stress can be combined with radiotherapy to treat cancer. For example, dhalcomoracin has been shown to inhibit cell proliferation and increases sensitivity to radiotherapy in NSCLC by inducing ER stress (Zhang et al 2020b). Phenethyl isothiocyanate in combination with Gefitinib induces apoptosis in NSCLC cells through ER stress-mediated Mcl-1 degradation (Zhang et al 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, drugs that activate ER stress can be combined with radiotherapy to treat cancer. For example, dhalcomoracin has been shown to inhibit cell proliferation and increases sensitivity to radiotherapy in NSCLC by inducing ER stress (Zhang et al 2020b). Phenethyl isothiocyanate in combination with Gefitinib induces apoptosis in NSCLC cells through ER stress-mediated Mcl-1 degradation (Zhang et al 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Han et al showed for the first time that chalcomoracin (5) treatment markedly promoted paraptosis along with extensive cytoplasmic vacuolation derived from the endoplasmic reticulum, rather than apoptosis, in PC-3 and MDA-MB-231cell lines [141]. Subsequently, Zhang et al demonstrated that chalcomoracin (5) could inhibit cell proliferation and increase sensitivity to radiotherapy in human non-small cell lung cancer cells also via endoplasmic reticulum stress-mediated paraptosis mechanism [142]. Takashi et al revealed that mulberrofuran G (31) could induce apoptotic cell death in HL-60 via both the cell death receptor pathway by stimulation of death receptor, and the mitochondrial pathway by Topo (162) were reported for the first times to possess HIF-1 inhibitory effect in the Hep3B cell-based assay [71].…”
Section: Antineoplastic Activitymentioning
confidence: 99%
“…However, radiation can also inhibit cell proliferation by disrupting the neoplastic cells physically through damage to the cell membrane and organelles, and thereby interfering with signal transduction (47)(48)(49). Damage to several organelles including the endoplasmic reticulum, ribosome, lysosome, and mitochondria have been implicated in the effects of RT-induced tumor cell death (50)(51)(52)(53)(54)(55)(56)(57)(58)(59).…”
Section: Effects Of Radiation Therapy: Cellular Damagementioning
confidence: 99%